Change the Qualis Criteria! - Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Since CAPES published its revised QUALIS criteria, the Brazilian Medical Association (AMB - Associação Médica Brasileira) has been organizing a series of meetings, held at its headquarters in São Paulo, Brazil, starting in August of 2009, in partnership with the Brazilian Association of Scientific Editors (ABEC - Associação Brasileira de Editores Científicos). [...]